Targeting synaptic plasticity to bridge translational gaps in sepsis-associated encephalopathy - Koji Hoshino (Frontiers in Aging Neuroscience)
Sepsis-associated encephalopathy (SAE) is a frequent yet underrecognized complication of sepsis that significantly contributes to long-term cognitive dysfunction in survivors. Despite advances in sepsis management, there is currently no established therapy targeting SAE, and translational gaps between basic and clinical research persist. Rodent models of sepsis suffer from variability in immune responses and poor translational fidelity. Moreover, behavioral tests commonly used to assess cognition in animal models are often confounded by sepsis-induced sickness behaviors and depression-like phenotypes, especially during the acute phase. Given these limitations, targeting synaptic plasticity—both mechanistically and therapeutically—has emerged as a promising approach. Accumulating evidence indicates that SAE arises from neuroinflammation triggered by systemic inflammation, in which activated microglia and subsequent cytokine signaling contribute to neuronal dysfunction and lead to impaired hippocampal long-term potentiation (LTP), a fundamental mechanism of learning and memory. Importantly, electrophysiological studies have shown that LTP impairment occurs within hours to days after sepsis onset, highlighting its potential as an early and sensitive biomarker for SAE. Recent experimental interventions, including low-intensity exercise, environmental enrichment, and modulation of gut microbiota, have shown beneficial effects on SAE. These findings underscore the need for integrative, multimodal strategies that address the complex pathophysiology of SAE. Synaptic plasticity, particularly LTP, may serve not only as a functional readout of neuroinflammatory damage but also as a modifiable target for early intervention. This review highlights the translational challenges in current SAE research and advocates for a paradigm shift toward mechanism-driven and plasticity-focused therapeutic development.